Laparoscopic management of ileal enterolith in abdominal tuberculosis: a case report and literature review - Kumar, Supreet; Gupta, Sonam; Tandon, Vivek; Govil, Deepak (International Surgery Journal, 2025)
Enterolithiasis is a rare condition characterized by the formation of stone-like concretions within the gastrointestinal tract. While commonly reported in the duodenum and colon, its occurrence in the ileum is rare and typically associated with intestinal stasis caused by pathological conditions such as Crohn’s disease, strictures, or tuberculosis. Enterolithiasis in the setting of abdominal tuberculosis is exceptionally uncommon and poses significant diagnostic and therapeutic challenges. This report presents the case of a 60-year-old female with a history of abdominal tuberculosis on anti-tubercular therapy, presenting with recurrent subacute intestinal obstruction. Radiological investigations revealed a calcified intraluminal mass in the distal ileum. An initial attempt at enteroscopic retrieval failed due to luminal narrowing. She subsequently underwent laparoscopic segmental ileal resection with extracorporeal isoperistaltic anastomosis. Postoperative recovery was uneventful. Histopathology confirmed healed tuberculous ileitis without granulomatous activity or features of Crohn’s disease. Ileal enterolithiasis should be considered in tuberculosis-endemic regions when evaluating unexplained or recurrent small bowel obstruction. Early imaging, high clinical suspicion, and prompt surgical intervention are critical. This case highlights the importance of differentiating tuberculosis-related strictures from other causes and supports laparoscopic resection as a safe and effective therapeutic strategy.